ON NEW CESARO-ORLICZ DOUBLE DIFFERENCE SEQUENCE SPACE - OGUZ OGUR; CENAP DUYAR (Romanian Journal of Mathematics and Computer Science, 2014)
The aim of this paper is to introduce the Cesaro-Orlicz double difference sequence space Ces_M^{(2)}(△, p). We study some topological properties of this space and give some inclusion relations